Comparison of Antibacterial Efficacy of Combination of Turmeric and Calcium Hydroxide with Three Intracanal Medicaments against Various Endodontic Bacteria: An in vitro Study - Upadhyay, Kanchi; Kencheppa, Mallikarjuna; Gupta, Shilpi; Sharma, Priyamvada; Roy, 5Soumik; Gupta, Puneet (Journal of Orofacial Research, 2015)
Introduction: An intracanal medicament have an antibacterial effect on the root canal flora. The effectiveness of different available intracanal medicaments and search for new antibacterial agents to use as intracanal medicament to ensure success of our treatment is today’s need. Curcumin (diferuloymthane) main yellow bioactive component of turmeric has wide spectrum of biological actions and this provides a basis for exploring its endodontic applications. Aim: To determine antibacterial efficacy of Curcuma longa (turmeric) against root canal microorganism and compare its  efficacy with calcium hydroxide, calcium hydroxide+ turmeric and metapex. Materials and methods: For an antibacterial assessment samples were divided into four groups as group 1 calciumhydroxide group 2 calcium hydroxide + turmeric oleoresin group 3 turmeric oleoresin group 4 metapex. Each group was tested against following root canal pathogens S. aureas, E. coli, E. feacalis by agar well diffusion method. Inhibition zone was recorded at 24, 48 and 72 hours. Results were tabulated andsent for statistical analysis. Result: Maximum inhibition of E.feacalis, E.coli, S. aureas is shown by combination of turmeric oleoresin and calcium hydroxide, i.e., group 2 followed by group metapex and then calcium hydroxide. Conclusion: Turmeric extract has substantial antibacterial effect and its combination with calcium hydroxide increases its antibacterial efficacy against all important root canal pathogens. So turmeric has great potential to be used as intracanal medicament